Method And Technology For Applying A Semi-Structured Data Classification Model In A Corporate Information System (Texas Journal of Engineering and Technology, 2024)
A scheme for solving the problem of binary clustering of incoming data in the control system is proposed. Methods of sequential shortening and sequential merging of clusters, as well as the model of initial placement of clusters are considered. Estimating the number of clusters is given to solve the clustering problem. A binary clustering method has been proposed for points in a circle. Based on the results of the research, the clustering practice was performed and the developed model and algorithms were implemented